Modeling the critical rotation speed of a bladed rotor with bent blades in a circulation mixer of feed mixtures - T. M. Kovaleva; S. M. Vedishchev; V. Yu. Zaitsev; V. V. Konovalov (Аграрная наука Евро-Северо-Востока)
The purpose of the research is to substantiate the critical rotation speed of a rotor with bent blades based on force analysis and modeling the movement of mixture particles in a horizontal loader of a circulation mixer. The research method[1]ology included the substantiation of the highest rotation frequency of the loader blade rotor based on a force analysis of moving particles of forces when they were moved by the bent blades of the loader and compliance with the conditions for the entry of flying particles into the tray. The numerical analysis performed on the basis of the obtained expressions using the Mathcad mathematical package made it possible to establish the critical values of the rotation speed of the rotor-loader with bent blades based on the condition of the material coming off the blade and the condition of the flight of particles from the blade into the receiving tray. With radial blades, the limitation is the entry of particles into the receiving tray at a critical frequency of 43 min-1 , then for a blade bend of 30° – about 60 min-1 , for a blade bend of 45° – about 70 min-1, for a blade bend of 60° – about 80 min-1. The lowest critical values of the rotor-loader rotation frequency from the condition of particle movement along the blade correspond to the blade bend angle of 27–60° and are determined by the friction coefficient of the material, amounting to 83–78 min-1. With an increase in material friction, the critical values of the rotor rotation speed from the condition of material coming off the blade decrease slightly, and the bend angle for the rotation speed extremum increases. The highest rotation speed of the rotor - loader with a radius of 0.12 m is limited to 78 min-1 at a blade bending angle of the order of 30–60°, determined by the friction of the material on the blade.